The Role of the Otherworldly and Real elements in Samuel Taylor Coleridge's The Rime of the Ancient Mariner (British Journal of Multidisciplinary and Advanced Studies, 2023)
Coleridge has offered his readers with a "nature and otherworldly" combination in his poetry that is both unique and impressive. Coleridge believes that man is surrounded by environment and that it is a special honour to be able to comprehend what he sees. Though written in the romantic style, The Rime of the Ancient Mariner is often considered as a masterwork of mystical poetry because to the poet's sense of wonder and the wide range of topics it addresses. On the other hand, it teaches its readership that no wrongdoing, no matter how little, will be tolerated. The article investigates how Coleridge balances earthly and otherworldly elements in the poem.